Design of Force Meter for Traction Unit - Gita Aprilyana; Endang Dian Setioningsih; Triwiyanto Triwiyanto (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Force gauge is an instrument used to measure the force on the traction unit. The purpose of this study is made a force gauge meter which used during traction operation. The main component of this force gauge meter is Atmega 328, HX711 module and Loadcell type S sensor. The mikrokontroller Atmega 328 is the main board. Loadcell type S used to detect the force of traction, and the module HX711 is used to amplify the output of the loadcell sensor. In this study, the measurements were performed in the hospital. The error of this design is 0.01% and 4.8% for minimum and maximum, respectively. The force gauge designed portable and comes with a battery indicator.